Rancang Bangun Sistem Informasi Surat Keterangan Lahir Menggunakan Metode Waterfall di Rumah Sakit X - Saputra, Riska Oktaviani; Syahidin, Yuda; Sari, Irda; Sukmawijaya, Jeri (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
A birth certificate issued by the hospital is the letter needed to obtain a baby's birth certificate at the population and civil registry office. At Hospital X, which is currently in the stage of implementing electronic medical records, it was found that there were problems related to the preparation of birth certificates, where delays often occurred and there was a lack of data that had not been included in the birth certificate. The purpose of this study was to design an information system for making birth certificates based on Microsoft Visual Studio 2012 in order to overcome delays and streamline the work of medical staff in making birth certificates. This study uses a descriptive examination technique. The process of collecting data in research through observation and interviews. The technique used in this design is through the waterfall development method and using software design with Data Flow Diagrams (DFD). The results of this system design make medical record management more accurate, effective and efficient in the activities of making birth certificates and processing birth data reports more quickly and precisely.